2005
DOI: 10.1007/s11030-005-3434-8
|View full text |Cite
|
Sign up to set email alerts
|

Microwave assisted IMDAF# reaction: Microwave irradiation applied with success to cycloaddition reaction of N-propargyl-N-p-tolyl-N-2-furfurylamines

Abstract: The new tertiary furfurylamine with triple bond as a dienophylic part i.e. N-(5-methyl-2-furfuryl)-N-prop-2-ynyl-p-toluidine (1) was prepared and the intramolecular Diels-Alder reaction of the amine (1) was performed under microwave irradiation conditions and by heating a benzene solution of the amine under nitrogen. Comparing the results of the usual thermal and the MAOS reaction, we confirmed our expectations that MAOS could promote the outcome of IMDA reaction of the suitably N-substituted tertiary 2-furfur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…Our theoretical studies revealed that the increased reactivity of ortho -substituted compounds is mainly due to a steric effect, which destabilizes the minimum conformation of the reactant compared to the active conformations . In order to improve the reaction with respect to less reactive starting materials, we have now turned to microwave chemistry, which to some extent has been applied in IMDAF reactions before . We herein report that not only was the reactivity in the Diels–Alder reaction greatly improved, also it is possible to carry out one-pot syntheses of dihydrophenanthridine and aza analogues, if the reaction is carried out in the presence of acid.…”
mentioning
confidence: 94%
“…Our theoretical studies revealed that the increased reactivity of ortho -substituted compounds is mainly due to a steric effect, which destabilizes the minimum conformation of the reactant compared to the active conformations . In order to improve the reaction with respect to less reactive starting materials, we have now turned to microwave chemistry, which to some extent has been applied in IMDAF reactions before . We herein report that not only was the reactivity in the Diels–Alder reaction greatly improved, also it is possible to carry out one-pot syntheses of dihydrophenanthridine and aza analogues, if the reaction is carried out in the presence of acid.…”
mentioning
confidence: 94%
“…Synthetic chemists are still trying to make the conditions for Diels–Alder reactions more environmentally friendly [ 48 58 ]. However, the number and variety of substrates in these studies is often limited, deep eutectic solvents are required and it is difficult to achieve both satisfactory product yields and the desired stereoselectivity [ 59 61 ]. The viscous nature of the aminofuranes usually requires the use of toxic solvents such as toluene, and in some studies, solvents such as DMSO, which are difficult to remove from the reaction medium [ 62 64 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yan zincir kısmında (tether de) N-KG ve O içeren furan çekirdekli bileşiklerin organik kimyada oldukça zor olan trisiklik ve tetrasiklik fused halkalaşma ürünleri tek adımda Termal ve mikrodalga yöntemle intramoleküler [4+2] Diels-Alder reaksiyonları sonucu elde edilebilmektedir [3,4].…”
Section: Introductionunclassified